2023
DOI: 10.3390/ijms24076650
|View full text |Cite
|
Sign up to set email alerts
|

Src-FAK Signaling Mediates Interleukin 6-Induced HCT116 Colorectal Cancer Epithelial–Mesenchymal Transition

Abstract: Colorectal cancer is one of the most prevalent and lethal malignancies, affecting approximately 900,000 individuals each year worldwide. Patients with colorectal cancer are found with elevated serum interleukin-6 (IL-6), which is associated with advanced tumor grades and is related to their poor survival outcomes. Although IL-6 is recognized as a potent inducer of colorectal cancer progression, the detail mechanisms underlying IL-6-induced colorectal cancer epithelial–mesenchymal transition (EMT), one of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…IFN-γ was found to synergize with TNF-α in inducing TJs disruption and ZO-1 deregulation, favouring both MLCK expression and activation in Caco-2 cells ( 53 , 71 , 72 ). IL-6, a critical pathogenic cytokine in several inflammatory diseases, including IBD ( 73 ), enhances intestinal epithelial permeability by impairing TJs integrity and downregulating E-cadherin expression ( 51 , 74 , 75 ). IL-22, a cytokine of the IL-10 family, whose levels increase in colonic tissues and in the peripheral blood of IBD patients ( 76 ), was found to increase TJs permeability ( 54 , 77 ) by downregulating the expression of both ZO-1 and E-cadherin ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ was found to synergize with TNF-α in inducing TJs disruption and ZO-1 deregulation, favouring both MLCK expression and activation in Caco-2 cells ( 53 , 71 , 72 ). IL-6, a critical pathogenic cytokine in several inflammatory diseases, including IBD ( 73 ), enhances intestinal epithelial permeability by impairing TJs integrity and downregulating E-cadherin expression ( 51 , 74 , 75 ). IL-22, a cytokine of the IL-10 family, whose levels increase in colonic tissues and in the peripheral blood of IBD patients ( 76 ), was found to increase TJs permeability ( 54 , 77 ) by downregulating the expression of both ZO-1 and E-cadherin ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Zhang et al ( 62 ), IHC analysis revealed that activation of STAT3 was conversely correlated with E-cadherin expression in HCC. In addition, it has been demonstrated that IL-6 treatment leads to E-cadherin downregulation in HCT116 colorectal carcinoma cells ( 69 ). Although there are two putative STAT3-binding sites in the E-cadherin promoter region, STAT3 may not directly bind to the E-cadherin promoter; instead, it may function via regulating the major EMT-TFs, including Snail, Slug, Twist and ZEB1, to influence E-cadherin expression ( 66 , 69 ).…”
Section: Role Of Stat3 Signaling In Emtmentioning
confidence: 99%
“…The activated ERK further promotes cell contraction and stimulates tumor cell movement by driving actin polymerization and edge protrusion adhesion turnover ( Samson et al, 2022 ). FAK has been identified as a significant regulatory factor for interleukin-6 induced EMT in colorectal cancer ( Huang et al, 2023 ). In DGC, the loss of CDH1 (encoding E-cadherin, a key regulator of the EMT) and RHOA Y42C mutation in gastric organs of engineered mice co-activate the FAK/AKT/β-catenin and YAP-TAZ pathways, promoting the transformation of normal gastric epithelial cells into highly invasive DGC cells ( Zhang et al, 2020 ).…”
Section: Role Of Fak In the Occurrence And Development Of Tumorsmentioning
confidence: 99%